плез 2. Упростите выражение : (а^(-4)/(4в^(-5) ) )^(-2)∙(а^6 в^2)/32
3. Вычислите значение выражения: (5^0∙〖25〗^(-7))/(〖125〗^(-6)∙5^1 )

вєлтикнадрей вєлтикнадрей    1   12.10.2020 04:02    1

Ответы
sohibjamol2008 sohibjamol2008  12.10.2020 06:01

Объяснение:

(a^(-4)/4b^(-5) * a6b²/32=   (4b^(-5)/a^(-4))² *a6b²/32=                                                                               =16b^(-10)/a^(-8) * a6b²/32 =   16a^6b^12/32a^(-8)=  1/2 a^14b^12

5^0*(5^(-7) / 125^(-6 *5^1=     1*(5²)^-7) / (5³)^(-6)*5^1=    5^-14 / 5^(-18)*5=     5^(-14) / 5^(-17)  =5^(-14-(-17)=    5^(-14+17)=  5³=  125

ПОКАЗАТЬ ОТВЕТЫ